POLA MENSTRUASI REMAJA SMAN X KAMPAR KIRI TENGAH - sukarni sukarni; putri wulandini; Hidayatun Nafiahh (LPPM Universitas Abdurrab, 2023)
Menstruation is a physiological change in a woman's body that occurs periodically and is influenced by reproductive hormones. This period is important in reproduction. Ideally, the menstrual cycle should be regular every month with a span of 28-35 days for each menstrual period. Menstrual cycle is said to be abnormal if < 28 days and > 35 days . This study aims to describe menstrual patterns in high school adolescents. This type of research is quantitative with a descriptive research design. The population of this research is high school youth, by cluster sampling. The research instrument used a questionnaire. The results of this study showed that the majority of adolescents in SMA N X Kampar Kiri Tengah experienced normal menstrual patterns, namely 104 respondents (62%), and abnormal menstrual patterns, namely 64 respondents (38%). Suggestion: The results of this study can be useful for the community, especially students of SMA N X Kampar Kiri Tengah to know the importance of menstrual patterns, so that it can be an early anticipation to prevent menstrual pattern disorders in adolescent students of SMA X Kampar Kiri Tengah